Answer: The amount that patty and ales paid including taxes was $40.96.
Step-by-step explanation:
To calculate the cost of the shirt and sweater together, we first calculate the total cost of shirt and sweater individually.
Shirt of $14.50 + 9% tax
Tax paid =
Amount of tax paid = ($14.50 × 0.09) = $1.305
Amount paid by patty = $14.50 + $1.305 = $15.805
Sweater of $22.95 + 9% tax
Tax paid =
Amount of tax paid = ($22.95 × 0.09) = $2.0655
Amount paid by ales = $22.95 + $2.0655 = $25.0155
Hence, the amount that patty and ales paid including taxes was $40.96.
The equation will be:
Why?
Let's work with your friend equation in order to find the time from his house to the restaurant (is the same as yours).
We are given the following function:
When: our friend arrived, so, calculating "x", we have:
We have that it took 5 hours for our friend to arrive at the restaurant, and it's the same time for you. We know that you live 100 miles from the restaurant.
Your equation will have the following form:
Where,
y is the position
k is the rate distance/time
x is the time
Now, again, when , you will have arrived at the restaurant too, so:
Using "x" equal to 5 hours, because you will have arrived at that time too, we have:
Your equation will be:
Have a nice day!
of the blue prism. Which statement is true?
a)The height of the red prism is one-third the height of the blue prism.
b)The height of the red prism is the same as the height of the blue prism.
c)The height of the red prism is six times the height of the blue prism.
d)The height of the red prism is three times the height of the blue prism.
Answer:
d) the height of red prism is three times the height of the blue prism.
Step-by-step explanation:
i) the volume of a rectangular prism is given by area of base height.
ii) volume of the blue prism is = (base of blue prism) (height of blue prism)
iii) volume of red prism is = (base of red prism) ( height of the red prism)
= ( base of blue prism) ( height of red prism)
iv) it is also given that
volume of blue prism = volume of red prism
⇒ (base of blue prism) (height of blue prism) = (base of red prism) (height of red prism)
⇒(base of blue prism) (height of blue prism) = ( base of blue prism) (height of red prism)
⇒ (height of blue prism) = (height of red prism)
∴ height of red prism = 3 height of blue prism
Therefore the correct option is
d) the height of red prism is three times the height of the blue prism.